Elastocaloric effect in vulcanized natural rubber and natural/wastes rubber blends. (30th November 2021) - Candau, Nicolas; Vives, Eduard; Fernández, Ana Inés; Maspoch, Maria Lluïsa
Abstract: Vulcanized natural/wastes rubber blends were prepared and their elastocaloric properties were analysed. A thermodynamic frame was used to discriminate the contributions of thermoelastic effects and strain induced crystallization/melting. The substitution of 20 wt% of the natural rubber matrix by waste rubber particles resulted in a maintain and even a slight improvement of heat exchanges (+10%), that we ascribed to a (i) high thermoelastic effect and a (ii) a high ability of the natural rubber matrix to crystallize due to a nucleation ability of the waste particles, both resulting from a strain amplification in the rubber phase due to undeformable carbon black aggregates in the waste particles. The materials coefficient of performance, COP mat, was estimated equal to 4.4 for the neat natural rubber and 3.8 for the blend containing 20 wt% of wastes due to larger mechanical energy originated from reinforcing effect of waste particles. Nonetheless, the elastocaloric (eC) abilities of these materials, especially their wide temperature spans (similar to those in films or polycrystals using rare earth elements) make these natural/waste rubber blends good candidates for application such as heating/cooling machines. Moreover, the partial replacement of natural rubber, a bio-source material showing risks of shortage, by industrial wastes rubber, place these blends as promising eco-friendly materials with high added value. Graphical abstract: Image 1 Highlights: Preparation of natural rubber (NR) containing ground tire rubber particles (GTR). NR/GTR blends show giant elastocaloric effect (eC) comparing the one in NR. eC is ascribed to thermoelastic effects and strain induced crystallization (SIC). eC is improved in presence of GTR particles up to a content of 20 wt.%.